Computing, Communication and Signal Processing Proceedings of ICCASP 2018 - Iyer, Brijesh; Nalbalwar, S.L.; Pathak, Nagendra Prasad; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book highlights cutting-edge research on various aspects of human-computer interaction (HCI). It includes selected research papers presented at the Third International Conference on Computing, Communication and Signal Processing (ICCASP 2018), organized by Dr. Babasaheb Ambedkar Technological University in Lonere-Raigad, India on January 26-27, 2018. It covers pioneering topics in the field of computer, electrical, and electronics engineering, e.g. signal and image processing, RF and microwave engineering, and emerging technologies such as IoT, cloud computing, HCI, and green computing. As such, the book offers a valuable guide for all scientists, engineers and research students in the areas of engineering and technology. .
Realization of Bandpass Filter Based on Spoof Surface Plasmon Polariton Technique at Microwave Frequency -- Design of Spoof Surface Plasmon Polaritons Based Transmission Line at Terahertz Frequency -- Multi-band Multi-mode Filter for Wireless Applications -- Design of Graphene based THz Antennas -- Concurrent Dual-Band Double-Layer High Gain Planar Antenna for WAICs / ITS Application -- Compact Rat Race Coupler Based Microstrip Balun without any isolation port -- Application of the Fractal Defected Ground Structure in Design of the Bandpass filter.
Keywords: Signal processing; Application software; Telecommunication; Signal, Speech and Image Processing; Computer and Information Systems Applications; Communications Engineering, Networks